Integrated optimisation model for neutral section location planning and energy‐efficient train control in electrified railways. Issue 18 (19th January 2021) - Miao, Rui; Wu, Chaoxian; Zhu, Kuan; Xue, Fei; Tian, Zhongbei; Hillmansen, Stuart; Roberts, Clive; Lu, Shaofeng
Abstract : Discontinuously electrified sections, such as neutral sections (NSs) widely exist in modern electrified railways. As a special arrangement of insulator, NSs with no electricity supplies are set up to ensure the two sections are kept electrically separate. This paper proposes a distance‐based mixed‐integer linear programming (MILP) model to incorporate both NS location planning and energy‐efficient train control (EETC) problem and concurrently optimise the NS location and train speed trajectory. The main contribution of this study is that based on the proposed integrated model, a number of case studies are conducted to investigate on the impact mechanism of NS locations on the total energy consumption of train operations. The optimisation results show that the energy saving rate in comparison with the worst cases is ranging from 1.9% to 6.1%% in various scenarios and significant saving rate can be achieved via planning the NS to be located in coasting areas as determined by EETC. In conclusion, the energy‐saving effect of the optimal NS location planning on the total energy consumption largely depends on how the NS‐triggered forced coasting is located in the journey and NS locations near stations and switching areas of speed limit lead to significant energy increase for bi‐directional journeys.